Peran Bahasa Prancis Agrowisata bagi Stakeholder Pariwisata di Toraja sebagai upaya Peningkatan Pelayanan Bidang Pariwisata terhadap Wisatawan Eropa - Hasyim, Muhammad; Armin, Mardi Adi; latjuba, ade yolanda; kuswarini, prasuri; masdiana, masdiana; hasbullah, hasbullah (JURNAL ILMU BUDAYA, 2017)
This paper discusses alternative solutions provided in tourism development in Toraja, after the monetary crisis since 1998, which has adversely affected tourism in Toraja, which is marked by a decrease in the number of foreign tourist arrivals.Based on the results of research that has been done in 2016, drawn the conclusion is the root of the problem against the tourism business in Toraja is the lack of variation of tourist attraction, which during this time, tourism is always a mainstay is the tradition culture: Rambusolo and traditional house "Tongkonan". Based on the results of interviews with respondents (foreign tourists who visit Toraja), found a solution that is the need for a variant of tourism objects that support Toraja main tourist attraction. Potential variation of objects to be developed in Toraja is agro-tourism, where Toraja already owns agricultural land, for example coffee plantations, cloves, cocoa that have not been cultivated as tourist attraction.One of the solutions done for the development of agro-tourism in Toraja, especially to tourism stakeholders provides French-speaking skills in the field of agrotourism in the form of training. One of the reasons for this activity is that the majority of foreign tourists visiting Toraja are from Europe who use French as the language of communication. The results of these activities resulted in three competencies: the knowledge of French in the field of agrotourism, the French language skills in agrotourism and the attitude that has a sense of responsibility in providing services to foreign tourists through the use of French Key words: agrotourism, tourist, coffee, tradition culture,  Toraja, Tongkonan